The creation of an individual panel using administrative tax microdata in South Africa - Amina Ebrahim; Chris Axelson (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
The availability of anonymized individual tax return data can contribute to a deeper understanding of the drivers behind the high levels of inequality and unemployment in South Africa. In the recent past, researchers have examined either payroll or personal income tax data. This paper explains the methodology behind the creation of an anonymized individual panel combining these data to produce a more complete overview of formal employment in South Africa. This paper provides a descriptive overview of the characteristics of the panel, notes some of the pitfalls in the data, and offers some ideas for research to highlight some of the potential.
Keywords: C81; 330; tax data; administrative data; individual panel